Quercus ×numidica Trabut (Fagaceae, Quercoideae) and Cynosuro peltierii-Quercetum afaredis Laribi 2000 new taxon and syntaxon to Kroumirian oak forests of Tunisia with remarks on their ecology and conservation - El Mokni, Ridha (Hacquetia, 2021)
The very little-known Quercus ×numidica Trabut, recently typified and synonymised to Q. ×kabylica Trabut, was found within the Cynosuro peltierii-Quercetum afaredis Laribi ex El Mokni ass. nov. (Quercion suberis Loisel 1971). Both the taxon and the syntaxon are described here for the first time for the oak forests of Kroumiria in Tunisia. The distribution, ecology and field photographs of the new taxon are presented and IUCN Red List assessment is provided in this paper. Threats at the national level are assessed and conservation measures for the species are proposed.